The Effect Of Eps, Roe, Der, Per, Pbv, Dy On The Share Price Of Bumn Companies Listed On The Idx - Anugrah, Jammes Irman Nur; Anggraeny , Shinta Noor; Wibawa , Koerniawan Dwi (Indonesian Scientific Publication, 2024)
Although they offer large potential for profit, stocks can also carry a high level of risk. Investors should evaluate the financial ratios of companies seeking financing, as failing to do so could result in investors losing out on capital that is projected to give a higher nominal return. The purpose of this study is to ascertain how stock prices are impacted by the following factors: Earning per Share (EPS), Return on Equity (ROE), Debt to Equity Ratio (DER), Price to Earning Ratio (PER), Price to Book Value (PBV) and Dividend Yield (DY). The classic assumption test, which includes the autocorrelation, multicollinearity, heteroscedasticity, and normalcy tests, is the data analysis method employed. Next comes hypothesis testing, which includes multiple regression analysis, the F test, the t test, and the determination test. The results showed, of the 6 financial ratios that had a partial effect were Earning per Share (EPS) and Price to Book Value (PBV), and all financial ratios had a joint effect (simultaneously) on stock prices. According to the determination test (R2) results, 49.5% of the sample was influenced by factors not included in the study, whereas 50.5% of the sample contributed. This is due to the fact that different investors employ different strategies, hence not all investors rely solely on financial ratios. Nonetheless, investors do not always employ specific strategies because investing is not always done for financial gain.